Supplier Relations and Control in the Malaysian Automotive Industry - Abdul Kadir, Kadzrina; Ahmad Arshad, Darwina; Johari, Johanim (2024)
This research examines the archetypes of buyer-supplier-supplier relationships within triad supply networks in the Malaysian automotive industry. Existing literature indicates that such triad relationships, involving buyers and two suppliers, are pivotal to supplier relations in the industry. In Malaysia, where the automotive industry is protected, this triad relationship may differ structurally. Through multiple-case studies, this research explores the opinions of interviewees on buyer-supplier relationships, focusing on control over business processes. The findings suggest that in these triads, various levels of control exist, and that competition between suppliers, facilitated by the buyer, is feasible if both parties' capabilities are developed